A Review of the Effects of Electrode Fabrication and Assembly Processes on the Structure and Electrochemical Performance of 2D MXenes. (9th August 2020) - Orangi, Jafar; Beidaghi, Majid
Abstract: MXenes are 2D materials with relatively high surface areas, high electrical conductivities, functional transition metal surfaces, tunable surface chemistries, and solution processability. Due to these properties, 2D MXenes have attracted widespread attention as electrode materials for energy storage devices, including electrochemical capacitors, with high power and energy densities. However, many studies have shown that the electrochemical performance of MXene electrodes is considerably affected by their structure and morphology. These properties are, for the most part, controlled by the method used for the assembly of 2D MXene flakes and the electrode fabrication methods. A successful electrode assembly and fabrication method should address several challenges, such as the restacking of 2D flakes, to achieve electrode structures and morphologies that deliver high ionic transport properties, electrical conductivity, and mechanical stability. This review aims to provide insight into the current state‐of‐the‐art assembly and fabrication methods used to design and fabricate high performance electrodes based on MXenes. The major challenges to be addressed and possible future directions in the fabrication of MXene electrodes for practical energy storage applications are highlighted. Abstract : Morphology and structure can significantly influence the electrochemical performance of electrodes used in batteries and supercapacitors. This review discusses recent advances in engineering the structure of electrodes based on 2D MXenes to boost their ionic and electronic transport properties. Electrode fabrication methods and assembly processes are reviewed and compared and future research needs in this area are discussed.